2021
DOI: 10.1016/j.micpath.2020.104642
|View full text |Cite
|
Sign up to set email alerts
|

Virulence, resistance and clonality of Proteus mirabilis isolated from patients with community-acquired urinary tract infection (CA-UTI) in Brazil

Abstract: Urinary tract infections (UTIs) are among the most common human infections, both in hospitals and in communities. Proteus mirabilis is known to cause community-acquired urinary tract infection (CA-UTI) and is an important causative agent of nosocomial UTIs. The pathogenesis of this species is related to its ability to manifest virulence factors, such as biofilms, adhesion molecules, urease, proteases, siderophores, and toxins. In this study, we investigated the virulence, sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
3
9
1
Order By: Relevance
“…In this study, we evaluated the molecular characteristics of P. mirabilis isolated from CAUTI. The result of the current study showed that all of the isolates had the ability of biofilm formation, being in line with other studies [ 30 , 35 ]. The severity of biofilm formation depends on the day of catheterization.…”
Section: Resultssupporting
confidence: 92%
“…In this study, we evaluated the molecular characteristics of P. mirabilis isolated from CAUTI. The result of the current study showed that all of the isolates had the ability of biofilm formation, being in line with other studies [ 30 , 35 ]. The severity of biofilm formation depends on the day of catheterization.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, a previous recent study in Egypt indicated 64.5% resistance to ampicillin, but a lower resistance rate (19.4%) to trimethoprim-sulfamethoxazole [11]. Our results are in accordance with previous studies from different parts of the world that also reported high resistance rate to these two antibiotics [5,[31][32][33]. This might be explained by the extensive misuse of these drugs in the treatment of UTIs.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of MDR in P. mirabilis reported varied among studies. Although a higher percentage of MDR was stated in Mirzaei et al [21] and Alabi et al [31] (82.5% and 55.6% respectively), Oliveira et al [32] and Mirzaei et al [33] reported a lower multidrug resistance percentage of 7.1% and 14.5% respectively. These discrepancies might be related to variances in in the sources of samples and regional differences in the abundance of bacterial strains and variable standards and controls for antibiotic prescription and use.…”
Section: Discussionmentioning
confidence: 75%
“…Resemble results of (Danilo de Oliveira et al, 2021); showing that the highest resistance rate was found to trimethoprim/ sulfamethoxazole combination. A study performed by (Gravey et al, 2017) showed different resistance rates for gentamicin (18%), phosphomycin (19%), ciprofloxacin (21%), norfloxacin (22%), nalidixic acid (26%), trimethoprim/ sulfamethoxazole (32%), ampicillin and amoxicillin (40%), and ticarcillin (42%) (Gravey et al, 2017).…”
Section: Pcr Detection Of Resistance Genesmentioning
confidence: 99%